Bounding Paganism: Who and What is In and Out, and What does this Reveal about Contemporary Kinship-Entangled Nature Spiritualities? - Taylor, Bron (Journal for the Study of Religion, Nature and Culture, 2023)
Paganism is a construction that religionists and scholars alike define according to their understandings and purposes. Herein I seek to explode common understandings of Paganism, which assume it always involves beliefs and practices about putatively divine natural entities, beings, or forces, and to consider such phenomena more broadly, as a sensory and affective sensibility – and a perception that is often entirely naturalistic (e.g., scientific and agnostic if not avowedly atheistic) – about the proper place of humans in, and obligations to, nature. When understood in this way one can discern that a host of cultural creatives, including those orchestrating pageants and ritual-resembling ceremonies, artists of all sorts, curators of science museums, and even some developers of theme parks, have affinity with Pagan worldviews and values. By expanding the boundary of what many confine as Paganism it becomes possible to consider whether Paganism is more widespread, and growing more rapidly, than many perceive.